Understanding level of General Takaful and Family Takaful among 3rd semester of ACIS students in UiTM Shah Alam / Muhammad Hamizan Fahmi Omar - Omar, Muhammad Hamizan Fahmi (2019)
Takaful is a system of islamic insurance that based on the principle of ta’awun (mutual cooperation) and tabarru’ (donation), where the risk is shared collectively and voluntarily by members of a group. The purpose of this study is to determine the level of understanding among ACIS students in UiTM Shah Alam about the takaful concept which is general takaful and family takaful. The total number of student involved is 71 people (population) and the method that has been used are quantitative that is a questionnaire through the google form. As the result, it showed that the student of ACIS had a moderate level of understanding of takaful concept on the objectives of the study. In conclusion, there is still a lot of effort and knowledge in other to understand about the concept of takaful especially to the whole society.